2016
DOI: 10.2991/jrnal.2016.3.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of UR-System 2 for Recovery of Motor Function of Plegic Upper Limb after Stroke

Abstract: The first author has developed TANABE therapy for severe hemiplegic stroke patients. In this paper we developed a training system (UR-System-PARKO) on the basis of TANABE therapy. The clinical test of the therapeutic effect of the UR-System-PARKO was performed in severe plegic hand. The results show the effectiveness of the training by the UR-System-PARKO for recovery of motor function for finger extension of the severe plegic hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Proprioceptive neuromuscular facilitation (PNF) is thought to be one of the most common neurophysiological techniques used by physiotherapists in rehabilitation after a stroke. Although less studied compared to other rehabilitation methods such as mirror therapy and virtual reality, recent studies have shown that PNF is one of the effective physiotherapy methods that facilitate stroke patients' recovery and can effectively improve upper limb function (Tanabe et al, 2016). However, to date, based on the available information, no systematic review can be identified that investigated the effect of the PNF technique in improving upper limb function in patients after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Proprioceptive neuromuscular facilitation (PNF) is thought to be one of the most common neurophysiological techniques used by physiotherapists in rehabilitation after a stroke. Although less studied compared to other rehabilitation methods such as mirror therapy and virtual reality, recent studies have shown that PNF is one of the effective physiotherapy methods that facilitate stroke patients' recovery and can effectively improve upper limb function (Tanabe et al, 2016). However, to date, based on the available information, no systematic review can be identified that investigated the effect of the PNF technique in improving upper limb function in patients after stroke.…”
Section: Introductionmentioning
confidence: 99%